QUANTITATIVE DETERMINATION OF PHYTOCHEMICAL CONSTITUENTS OF FRACTIONS OBTAINED FROM Ficus asperifolia LEAVES MIQ (MORACEAE) AND THE CHARACTERIZATION OF COMPOUNDS IDENTIFIED IN THE RESIDUAL AQUEOUS FRACTION - Abdullahi, Ibrahim Doma; Yahaya, Umar Hauwa; Suleiman, Umar Bello; Abubakar, Abdullahi Rabiu; Maitama, Adamu Yusuf; Abdullahi , Rahana Ameera; Yaro, Abdullahi Hamza (FUDMA JOURNAL OF SCIENCES, 2023)
Ficus asperifolia (Miq), family Moraceae is popularly known as sand-paper tree that is found in marshy areas around river banks. In Nigeria, it is called kawusa by Hausa tribe, ipin by Yoruba tribe and asesa or amerenwa by Igbo tribe. This research aims to quantify secondary metabolites present in the crude methanol extract and fractions and to characterize the identified compounds in the residual aqueous fraction of Ficus asperifolia leaves. The powdered fruit was extracted using 6L of 70% methanol. The crude extract was dissolved in water and fractionated using chloroform, ethylacetate, and n-buthanol. Phytochemical screening was conducted to determine the chemical composition of crude methanol leaf extract of Ficus asperifolia and its fractions. The phytochemical screening conducted revealed the presence of saponins, tannins, flavonoids, alkaloids, steroids and cardiac glycosides. Quantitative analysis of total alkaloids, flavoniods, saponins, and cardiac glycosides was also carried out. The crude extract fractionated produced 16.5% of chloroform, 6.8% of ethylacetate, 5.9% of n-butanol and 70.8% of residual aqueous fractions. The extract was further characterized using the available spectroscopic techniques such as FT-IR, UV, and GC-MS respectively.
Keywords: Fractionation; Phytochemical; Quantitative; Metabolites; Ficus asperifolia